ANALYSIS OF CRITICAL THINKING IN CLASS 4 STUDENTS OF SDN 2 KUTOSARI IN THEMATIC LEARNING 2013 CURRICULUM - Marchelina Dwi Saputri; Kartika Chrysti Suryandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Thematic learning in 2013 curriculum  has competence time front that is ability thinking clear and critical. Student could said have ability critical thinking if they pass by 6 steps of Critical thinking.  So this study was a purpose was to analyze critical thinking in class 4 students of SD N 2 Kutosari in thematic learning 2013 curriculum. This study used descriptive qualitative method. The research subjects were the fourth grade studenst of SD N 2 Kutosari. Data collection though observation, documentation and interview to the fourth grade student. Result research show ability critical thinking of class 4 student of SDN 2 Kutosari already exists, but students do not always think critically but only in limited learning. conducted students begin to be critical with 47,72% of students able to think critically. So the teacher lures students to think critically based on six step of critical thinking